(untitled) (Swiss Medical Weekly, 2021)
Atopic dermatitis is a chronic inflammatory skin disease characterised by eczematous skin lesions and intense pruritus. It is often associated with other atopic diseases such as allergic rhinitis and conjunctivitis, bronchial asthma and eosinophilic oesophagitis. Dupilumab is the first biologic approved for the treatment of moderate-to-severe atopic dermatitis in Switzerland. Dupilumab targets the interleukin (IL)-4/IL-13 receptor and thus inhibits the signalling of IL-4 and IL-13, two key mediators of type 2 inflammation, resulting in an improvement of clinical signs and symptoms of atopic dermatitis. Patients with atopic dermatitis present more often with ocular surface diseases (OSDs), such as allergic conjunctivitis, blepharitis and keratitis as well as infectious conjunctivitis and keratoconus compared with the general population. Upon dupilumab therapy, increased rates of ocular surface diseases have been reported in clinical trials. Interestingly, dupilumab-associated (da) OSD is restricted to atopic dermatitis patients and has not been observed in asthma and chronic rhinosinusitis trials. Fortunately, most cases of dupilumab-associated OSD are mild-to-moderate and transient. Thus, ocular surface disease presents a particular adverse event of treatment with dupilumab in dermatology. This article aims at providing a practical guide for physicians, with a special focus on dermatologists, allergists and ophthalmologists in Switzerland, to the diagnosis and management of dupilumab-associated OSD in atopic dermatitis patients. For this purpose, an expert group of dermatologists and ophthalmologists from university and cantonal hospitals in Switzerland reviewed data on ocular surface diseases published in clinical trial and real-life reports of dupilumab therapy, published case reports and case series on the management of dupilumab-associated OSD, as well as recent recommendations provided by experts of national and international boards. Based on the observations of dupilumab-associated OSD and practical experiences in identifying and treating OSD, an algorithm has been developed that is specific to the needs in Switzerland. Considering concomitant ocular diseases and differential diagnoses, the clinical presentation of dupilumab-associated OSD and its response to therapeutic measures, a stepwise approach is recommended. Mild dupilumab-associated OSD can be managed by dermatologists and allergists, whereas patients with moderate-to-severe OSD requiring corticosteroid or calcineurin inhibitor therapy should necessarily be referred to an ophthalmologist. The effects of preventive measures, such as artificial tears, are uncertain. The recommendations provided here should guarantee a prompt and effective treatment of OSD for patients under dupilumab therapy in order to prevent that an otherwise potent therapy has to be ceased because of ocular adverse events.